Aplikasi Kontrol PID Heat Exchanger Pabrik Etilen Glikol dengan Kapasitas 100.000 Ton/Tahun - Leni Maulinda; Chairun Nisa; Muhammad Muhammad (Jurnal Teknologi Kimia Unimal, 2019)
Heat exchangers are tools used to transfer heat energy between a solid surface and fluid or inside different particles and in thermal contact. The objective of the study was to determine the optimum values of Kc, Ti and Td which were applied to the control equipment of the ethylene glycol preparation exchanger. This research also uses design expert software to help get optimum vlue of Kc, Ti and Td before applied to PID system. Proportional-Integral-Derivative (PID) is a controller to determine the precision of an instrumentation system with the characteristics of feedback on the system. As the methodology of this research is to create a steady state Heat Exchanger model, then change the steady state model into a dynamic model, so create a PID model control, then tuning the PID control and testing PID controls, by disturbing the set point. The result of applying PID control system then got the fastest average time with value Kc = 3, Ti = 0,01 Td = 0,04 that is 0,77 minutes. At a temperature of 147.6 air vapor rate of 290.8 Kg / hr; at a temperature of 148.6 found velocity speed of 297.7 Kg / hr; At temperature 149.6 air vapor rate 305.0 Kg / hour; At a temperature of 149.7 air vapor rate of 305.8 Kg / hour and at a temperature of 150 air vapor rate of 308.1 Kg / Hour. Keywords:heat exchanger, PID, set point